Late antenatal booking and its predictors in Lundu district of Sarawak, Malaysia - Sam Froze Jiee,; Razitasham Safii,; Helmy Hazmi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction: Antenatal care is widely acknowledged as an effective tool to prevent adverse outcomes in antenatal mother and their children. In Malaysia, early entry to antenatal care refers to first visit within the 12th week of gestation. Delayed access to antenatal care has not been extensively studied in Malaysia, whereas several literatures reported high prevalence of late antenatal booking in the developing countries. The objective of this study was to determine factors and barriers associated with late antenatal booking and level of knowledge on timing of antenatal booking among child bearing age mother in Lundu District of Sarawak. Method: This was a cross sectional study among 284 pregnant women in all five Maternal and Child Health (MCH) Clinics of Lundu. Results: The prevalence of late antenatal booking in Lundu was 28.2%. Unmarried women were more likely to book their pregnancy late compared to the married women. The prevalence of late antenatal booking was also higher among the unemployed women than those who were employed. Respondents without their own income also tend to book their pregnancy later than those who had their own income. Significantly high percentage of late antenatal booking were also reported among those who never utilise any contraceptive method, unplanned their pregnancy, without past medical illness or history of complication in previous pregnancy and among those who has problem with marriage certificate. Those who booked their pregnancy beyond the 12th week of gestation also reported to have lower level of knowledge on antenatal booking as compared to those who started their antenatal care early. Conclusions: In conclusion, intervention strategies should be formulated and to be carried out in order to tackle issues related to late entry to antenatal care in order to prevent unwanted adverse outcome associated with delayed antenatal care.